Answer:
C
Step-by-step explanation:
We see that we can factor out 2x from the equation! So our equation becomes 2x(x-2) = 0.
Since the only way for things to multiply to equal to zero is if at least one of the numbers is 0.
So if x-2 is the 0, then x = 2.
If 2x is the 0, then x = 0.
So our answer is C. 0,2
Sorry that is not a linear model. There is not a constant rate of change. Are you sure you copied it correctly
Answer:
x = -8
Step-by-step explanation:
x = 2y - 4 --- Equation 1
7x + 5y = -66 --- Equation 2
I will be using the substitution method to solve this.
Substitute x = 2y - 4 into Equation 2:
7x + 5y = -66
7(2y - 4) + 5y = -66
Evaluate.
14y - 28 + 5y = -66
Evaluate like terms.
19y - 28 = -66
Isolate 19y.
19y = -66 + 28
= -38
Find y.
y = -38 ÷ 19
y = -2 --- Equation 3
Substitute y = -2 into Equation 1:
x = 2y - 4
x = 2(-2) - 4
Evaluate.
x = -4 - 4
x = -8
Answer:
4/3/8
Step-by-step explanation:
12/1/2-8/8/1
=25/2-65/8
=100-65/8
=35/8
=4/3/8
Answer:
2.26666666667 is the answer